2015
DOI: 10.4269/ajtmh.14-0295
|View full text |Cite
|
Sign up to set email alerts
|

G6PD Deficiency in an HIV Clinic Setting in the Dominican Republic

Abstract: Abstract. Because human immunodeficiency virus (HIV)-infected patients receive prophylaxis with oxidative drugs, those with glucose-6-phosphate dehydrogenase (G6PD) deficiency may experience hemolysis. However, G6PD deficiency has not been studied in the Dominican Republic, where many individuals have African ancestry. Our objective was to determine the prevalence of G6PD deficiency in Dominican HIV-infected patients and to attempt to develop a cost-effective algorithm for identifying such individuals. To this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…G6PD activity was measured by a Clinical Laboratory Improvement Amendments-certified (CLIA-certified) reference laboratory (Associated Regional and University Pathologists Laboratories). All 13 exons of the G6PD gene of G6PD-deficient volunteers were analyzed by next-generation sequencing in the CLIA-certified Personalized Genomics Laboratory at Columbia University Irving Medical Center, New York, New York, to identify the specific G6PD variant present (64).…”
Section: Methodsmentioning
confidence: 99%
“…G6PD activity was measured by a Clinical Laboratory Improvement Amendments-certified (CLIA-certified) reference laboratory (Associated Regional and University Pathologists Laboratories). All 13 exons of the G6PD gene of G6PD-deficient volunteers were analyzed by next-generation sequencing in the CLIA-certified Personalized Genomics Laboratory at Columbia University Irving Medical Center, New York, New York, to identify the specific G6PD variant present (64).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, among the participants with G6PD deficiency, we found 19.2% to harbor the G6PD A - allele (G202/A376), which is associated with the reduced enzyme activity [ 15 ]. A study by Xu et al in the Dominican Republic also reported a similarly high prevalence of the G6PD A - variant among HIV-infected patients [ 36 ]. Of note, we also observed that, among those with G6PD deficiency based on the methemoglobin reductase technique, 30.8% presented with no band on electrophoresis.…”
Section: Discussionmentioning
confidence: 95%
“…The prevalence of G6PD de ciency is relevant to both HIV and malaria. Despite HIV infection and antiretroviral therapy (ART) are both associated, separately and together, with increased oxidative stress, the impact of G6PD de ciency on the oxidative stress of people living with HIV (PLHIV) on ART is controversial [59][60][61] . PLHIV have signi cantly lower levels of antioxidants, hematology parameters, and CD4 + cells in comparison to healthy subjects; nonetheless, PLHIV on ART have presented higher level of antioxidants compared to ART naïve subjects 62 .…”
Section: Discussionmentioning
confidence: 99%